2010
DOI: 10.1080/17512780903306571
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Journalism

Abstract: The need to distinguish clearly the disciplines involved in quality reporting from the now universal capacity for conveying facts and opinions has never been more widely acknowledged. To date, attempts to classify the attributes of journalistic practice have encompassed professional traits or values, journalists' criteria of quality or excellence, and the elements or principles underlying journalism. This paper considers the utility of those streams of work for evaluating the practice of journalism and builds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Potential for bias can result in cases where the material cited is authored by an individual or organisation that receives funding or other support from the tobacco industry; from reports commissioned by the tobacco industry; and/or unsubstantiated interpretation of existing information. Objectivity of resources cited was largely determined by whether specific sources were peer-reviewed or, in the case of non-academic reports, met accepted norms of fairness and accuracy [29]. Data gathered were initially coded by country by respective authors (Australia, RM; Canada, AM and JS; the UK, BH; Netherlands, JE) and all data presented in Table 1 were then assessed by all authors for consistency and accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…Potential for bias can result in cases where the material cited is authored by an individual or organisation that receives funding or other support from the tobacco industry; from reports commissioned by the tobacco industry; and/or unsubstantiated interpretation of existing information. Objectivity of resources cited was largely determined by whether specific sources were peer-reviewed or, in the case of non-academic reports, met accepted norms of fairness and accuracy [29]. Data gathered were initially coded by country by respective authors (Australia, RM; Canada, AM and JS; the UK, BH; Netherlands, JE) and all data presented in Table 1 were then assessed by all authors for consistency and accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…In Shapiro's (2010) framework to evaluate newspaper quality, the dimension of "style" includes such elements as word choices and linguistic packaging. When looking at word choices and linguistic packaging, quality reporting is typically associated with presenting information in a sober style, while sensationalistic reporting can be considered the opposite (cf.…”
Section: Extending the Definition Of Sensationalism To Printed Newsmentioning
confidence: 99%
“…According to Urban and Schweiger (2014), high-quality journalists should be diverse in accurately representing social groups and socially relevant issues while upholding ethical, impartial standards. Professional journalists have mainly emphasized rigorous, independent reporting as a public service while news managers have frequently accentuated popular trivia as being the most saleable news (Beam et al, 2009; Hujanen, 2009; Schapiro, 2010; Soloski, 1989). Meijer (2001) has found that high-quality journalism can succeed in popular formats by providing a civic-oriented approach to inform public audiences about complex social issues.…”
Section: Literature Reviewmentioning
confidence: 99%